"The Danube area" - Optimistic perspective after the second world war - Kupa, László (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The present study deals with a few important points which were made in the three-volume work published as ĆThe Danube AreaĆ in 1946 edited by Elemér Radisics. Within its frames it deals with the optimistic post-World War II perspectives of the countires of the "Danube Area", the negative equilibration tendency working over the economic development of the region's states as well as its causes. The study examines the changes in the population ratio of the area concerning each country and it also deals with the course of Hungary's population on an international scale.
Keywords: Podonavje; povojno obdobje; gospodarski razvoj; prebivalstvo